2020
DOI: 10.1002/jsfa.10495
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation behavior, residue distribution and dietary risk assessment of cyromazine, acetamiprid and their mixture in cowpea and cowpea field soil

Abstract: BACKGROUNDCyromazine and acetamiprid are widely applied as pesticides in agriculture, causing increasing concerns about their residues in crops. In this study, cyromazine, acetamiprid and their mixture were applied to cowpea to investigate their degradation dynamics and perform a dietary risk assessment.RESULTSThe dissipation behavior of cyromazine and acetamiprid in the single‐ and mixed‐pesticide groups followed first‐order kinetics, with a linear correlation coefficient of 0.910 to 0.987. The half‐lives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Previous experiments reported half-lives of acetamiprid in the range of 1-2 days for plant matrices like rice (Saha et al 2017), okra (Singh and Kulshrestha 2005), mustard (Pramanik et al 2006) and tea (Gupta and Shanker 2008); however, comparatively higher half-lives (2-5 days) were reported in some literature for watermelon , cowpea (Fu et al 2020) and chilli ). For soil matrices, half-lives ranging from 5-10 days were generally found (Yu et al 2011) and in some cases, half-lives of more than 10 days were also observed (Fu et al 2020;). For buprofezin, the studies on plants and soil were limited and its persistence behaviour was found varying with various crops (Mohapatra et al 2020).…”
Section: Dissipation Kinetics and Waiting Periodsmentioning
confidence: 89%
“…Previous experiments reported half-lives of acetamiprid in the range of 1-2 days for plant matrices like rice (Saha et al 2017), okra (Singh and Kulshrestha 2005), mustard (Pramanik et al 2006) and tea (Gupta and Shanker 2008); however, comparatively higher half-lives (2-5 days) were reported in some literature for watermelon , cowpea (Fu et al 2020) and chilli ). For soil matrices, half-lives ranging from 5-10 days were generally found (Yu et al 2011) and in some cases, half-lives of more than 10 days were also observed (Fu et al 2020;). For buprofezin, the studies on plants and soil were limited and its persistence behaviour was found varying with various crops (Mohapatra et al 2020).…”
Section: Dissipation Kinetics and Waiting Periodsmentioning
confidence: 89%
“…The acute and chronic dietary risks posed by thiophanate-methyl and carbendazim were determined from the following equations: 35,40 NESTI=FI×HR=b:w:…”
Section: Dietary Risk Assessmentmentioning
confidence: 99%
“…Sufficient studies had demonstrated that acetonitrile had an appropriate polarity for most analytes, thereby generated higher recoveries and more minor co-extracted matrix components, such as pigments, proteins, lipids, and waxes (Xu et al, 2021;Fang et al, 2020;Fu et al, 2020). Consequently, acetonitrile was selected as the extraction solvent in this study.…”
Section: Optimization Of the Sample Extraction Proceduresmentioning
confidence: 99%
“…QuEChERS, a quick, easy, cheap, effective, rugged, and safe pre-treatment technology, greatly simplified the sample pre-treatment process and became the preferred approach for pesticide multi-residue detection (Anastassiades et al, 2003). Therefore, it had been widely applied to analyze the pesticides on several substrates such as grains, oilseeds, tea, vegetables, and fruits (Huang et al, 2018;Fang et al, 2020;Fu et al, 2020). Moreover, Sufficient researches had been established the determination method coupled with QuEChERS for some pesticides in Sichuan pepper samples, including the high-performance liquid chromatography-mass spectrometry (HPLC-MS) method for the detection of flumetsulam (Wang et al, 2017), gas chromatography (GC) to detect pesticides such as BHC, DDT, fenvalerate, deltamethrin, fenthion, and malathion (Peng and Yao, 2019).…”
Section: Introductionmentioning
confidence: 99%